MODAL TESTING AND FINITE ELEMENT MODEL UPDATING OF TWO NOMINALLY IDENTICAL CONCRETE BUILDING FLOORS - Widjaja, Taufik Ramlan (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
This paper describes a combined approach of modal testing and finite element (FE) analysis for vibration analysis of a structural system comprising two nominally identical concrete building floors located at adjacent levels. Initially, a field test of a full-scale joint two-level floor system was conducted to obtain the first five mode shapes and natural frequencies. Sensitivity-based FE model correlation and updating were then con-ducted to match the dynamic characteristics of the FE model with the experimental data. By setting certain indicators of good correlations between analytical and experimental models, an updated FE model comprising two nominally identical building floor was obtained.